Proposal for the training of flexible education in preschool and public educational stages in the Kingdom of Saudi Arabia - al-Zahrani, Hanan bint Ahmed bin Mishni (Journal of Educational and Psychological Sciences, 2019)
The aim of this study is to recognize the flexible education system in primary education stages and preschools in the Arab world. Along with the justifications for acknowledging such a system، including its contributions in solving the issues of the school education system and its application methods. This study is based on both descriptive and analytical approaches to analyses the findings by identifying the justifications for acknowledging this system، together with previous studies and successful examples، and make comparison between the traditional education and the flexible education system and this study was the tool in observation and analysis the stories،pictures and videos of learning experiment for families who adopt flexible education system and apply that in two public education schools and twenty flexible education systems. This study formed from observation and analysis eight points : the objectives of the educational process، the teacher، the curriculum، student needs، teaching strategies، educational environment and its preparation،educational speed and evaluation .And determination the advantages and disadvantages to everyone from these eight points . The results of the study according to the eight points above show that the flexible education system in primary education stages and preschools is outperform the traditional education system . They also show the reasons and justifications to experiment the flexible education system and its application methods . According to the result the study confirm to apply the flexible education system in primary stages and preschools in Saudi Arabia to keep up with modern educational systems، and for its benefits to society as a whole .